HISTORICAL SOURCES INCLUDE INFORMATION ON THE ACTIVITIES OF THE RULER OF SUGHD TARKHUN AND THEIR ANALYSIS - Boymirzaev Ismoiljon Khasanovich (Western European Studies, 2024)
This article presents sources and their analysis of the activities of Tarhun, one of the national leaders who fought against the invasion of the Arab Caliphate.
Keywords: Arabic-language sources; Tarhun; Ustrushona; Chaghaniyon